Can I Afford One More Candy? How Motivational Contexts Shape Adaptive Cognitive Control in Children. - Toffoli, Lisa; Calderan, Margherita; Del Popolo Cristaldi, Fiorella; Duma, Gian Marco; Calcagnì, Antonio; Pastore, Massimiliano; Tarantino, Vincenza; Mento, Giovanni (Developmental Psychology, 2026)
Recent findings suggest that preschoolers are capable of adapting cognitive control (CC) through bottom–up associative learning. However, it is not clear how motivational contextual triggers may influence this ability. This study investigated adaptive CC in a "hot" experimental context administering a modified version of the Balloon Analogue Risk Task to 170 children (83 F; 4–7 years). Specifically, a proportion manipulation induced different risky attitudes based on item-specific features (i.e., the balloon color). Overall, children were capable of inferring environmental regularities embedded in the context to optimize their performance. Regarding their ability to exploit and update these regularities for flexible CC adaptation, results suggest that reversal learning is ambiguous at the block level—overshadowed by a general increase in risk-taking—but tentatively present at the sub-block level, with asymmetric effects. Indeed, children seem to successfully adapt CC when going from a low to a high advantageous context but not vice versa. Moreover, different adaptive CC profiles were predictive of daily behavioral difficulties revealed by parental questionnaires. Public Significance Statement: This study suggests that even young children (4–7 years old) are able to use environmental regularities to adapt self-regulation. Importantly, this ability may differ as a function of contextual motivation and seem to predict daily behavioral difficulties as assessed using a parental questionnaire.